CHILD ABUSE - Aziz, Farida (Journal of Ayub Medical College Abbottabad, 2007)
When I started my job as a pediatrician in one of the teaching hospitals in Pakistan, I asked one of my colleagues ’˜Do you see child bettering in this country’? The prompt answer was... ’˜NO! We see wife bettering not child battering’. But as the days and months passed and an avalanche of human problems started emerging in front of my eyes, the situation was entirely different. How do we define child battering? Is it just physical abuse? The answer is no. Child abuse can be in many forms: Mental Abuse, Emotional Abuse Physical Abuse, Sexual Abuse, Moral and Ethical Abuse and perhaps in its most important and subtle form... Child Neglect.1 I found intentional and unintentional child abuse so common in its many forms with or without awareness by all concerned, that it was appalling; the concerned including older siblings, Parents, doctors and the society in general.